(untitled) (Revista Innova Educación, 2024)
The Lesson Study methodology is recognized as a powerful tool to strengthen teaching practice and learning globally. However, its effectiveness depends on overcoming cultural, structural, and methodological barriers. Therefore, it is crucial to investigate how and under what conditions it can be successfully implemented. This study analyzed the application of this methodology in various educational contexts, identifying key factors for its success and critical areas that require improvement to optimize its impact. The PRISMA protocol was followed, and a search was conducted in the Scopus, Web of Science, and ScienceDirect databases, selecting publications in English between 2010 and 2024. Initially, 1979 resources were identified, which were reduced to 39 empirical articles with the keyword "Lesson Study" in their title. The main findings indicate that this methodology is primarily applied in initial teacher training and professional development. Among the most common barriers are resistance to change and lack of time and resources. On the other hand, interdisciplinary collaboration, technology integration, and curricular adaptations are key facilitators. The most significant impacts include the improvement of pedagogical and disciplinary knowledge, critical teacher reflection, increased academic performance, attention to individual needs, and the promotion of meaningful learning among students. In conclusion, proper implementation of this methodology fosters the improvement of teaching strategies, student learning, and, consequently, educational quality.